Pinkalicious and the pinkatastic zoo day - Kann, Victoria (New York : Harper, 2012)
Pinkalicious and Peter attend Teddy Bear Day at the zoo and have problems with a monkey.
"1, beginning reading."
1.8
K-3
K-3
380L
Keywords: Zoos -- Juvenile fiction; Zoo animals -- Juvenile fiction; Zoos -- Fiction; Zoo animals -- Fiction; Zoos -- Fiction; Zoo animals -- Fiction; Readers (Elementary)